Management control in modern organizations - Sljivic, Slavoljub; Skorup, Srdjan; Vukadinovic, Predrag (International Review, 2016)
This paper deals with management control as an important instrument for managingperformances in modern organizations. The paper indicates to the circumstances in whichclassical theory of management control was created, and describes its process offunctioning, with the specifics in large organizations. The aim is to point to some openquestions and directions of further development of the management control, as well as to atleast partially fill the gap that exists in the domestic literature. The conclusion is that theexisting management control framework remains still valid. Open questions can be bestresolved within the concept that observes this matter as a "package" of different controlsystems, not just those that are oriented to accounting-based performance measures.